The Impact of Petroleum Tax Incentives on Foreign Direct Investment Inflow: Evidence from Nigeria - Kyari, Adam Konto (International Journal of Energy Economics and Policy, 2020)
Recent events in the Nigerian oil and gas industry has called to question the appropriateness of the Nigerian petroleum tax incentives in attracting foreign direct investments into the nation's oil and gas sector. There were instances of multinational oil companies relocating to other countries due to uncertainty of operating environment. As a result, this study investigates whether the Nigerian petroleum tax incentives package is appropriate in attracting foreign direct investments. Data was collected via a five point Likert questionnaire and analysed using descriptive statistics and Kruskal-Wallis technique. The study revealed, among others, that Nigeria's petroleum tax incentive package is sufficient in number and appropriate in mix in attracting foreign direct investment. This study concludes that Nigeria's petroleum tax incentive package is suitable in attracting foreign direct investments. Equally, the study concludes that the tax incentives is sufficient in number and appropriate in mix in attracting foreign direct investments in into the nation's oil and gas industry Finally, the study recommends further study on other possible ways of attracting inflow of FDI into the Nigerian oil and gas industry. Keywords: Foreign, investments, oil, gas, taxation, incentives JEL Classifications: F21, H21 DOI: https://doi.org/10.32479/ijeep.9187